Introduction to Digital electronics - Dueck Robert; Reid Kenneth J. (American : Thomson Delmar Learning, 2008)
The perfect introduction to digital concepts, applications, and design, Introduction to Digital Electronics uses a logical organization of topics, clear explanations, and current examples to present key information in a way that is easy to grasp. Unique in its approach, this book covers combinational and sequential logic circuits using CPLDs while still covering circuit design at the gate level using TTL/CMOS devices. The book begins by introducing combinational logic, including detailed explanations for implementing circuits in Altera Quartus II software and CPLDs. The material continues to be presented at the gate level, preparing readers to successfully navigate more complicated areas like functional circuits. Using formal problem-solving concepts, combinational design is then covered, which includes a large combinational design that includes the building and simulation of each component, marking a valuable departure from traditional books in the field which do not cover large-scale design at a combinational level. Additional coverage includes sequential circuits with an emphasis on relevant and useful circuits, and microprocessor and memory concepts.There are book including 13 chapter
Chapter 1: Basic principles of digital systems
Chapter 2: Logic functions and gates
Chapter 3: Boolean algebra and combinational logic
Chapter 4: Introduction to PLDs and Quartus II
Chapter 5:Combinational logic functions
Chapter 6: Digital Arithmetic and Arithmetic Circuits
Chapter 7: Digital System Application
Chapter 8: Introduction to Squential Logic
Chapter 9: Counters and Shift Registers
Chapter 10: State Machine Design
Chapter 11: Logic Gate Circuitry
Chapter 12: Memory Devices Systems and Microprocessors
Chapter 13: Interfacing Analog and Digital Circuits.
Keywords: Digital Electronics; Dueck--Robert K